Türk vergi hukukunda tebligat - Ayyıldırım, Kadir (My University, 2018)
Hakkında tesis olunan hukuki işlemi ilgilisine bildiren tebligat, hem adli hem idari süreçte çok önemli bir görev üstlenmektedir. Tebligat, vergiye ilişkin işlemlerde üzerinde hassasiyetle durulması gereken bir husustur. Zira tebligat, vergilendirme sürecine ilişkin işlemlerde muhatabının idari haklarını kullanmasına imkân tanımasının yanı sıra vergi yargılama sürecinde de muhatabının yargısal haklarını kullanabilmesine olanak sağlamaktadır. Bu bağlamda uzlaşma ve cezalarda indirim gibi idari hakların kullanılması, yalnızca tebligat işleminden sonra mümkün olabilmektedir. Ayrıca tebligat, ilgilisinin hem hakkında tesis olunan hukuki işlemden, hem de bu işlemin dayanağı olan hususlardan haberdar edilmesini sağlamasının yanı sıra, bu işleme karşı yargısal haklarını yargısal mercilerde arayabilmesine ve iddialarını bu mercilerde öne sürebilmesine de olanak tanır. Bu bakımdan tebligat, Avrupa İnsan Hakları Sözleşmesi md.6’da hüküm altına alınan adil yargılanma ilkesi ve bu ilkeyi temellendiren diğer ilkelerle yakından ilişkilidir.

Notification of the legal proceedings concerning the establishment takes on a vital role both in judicial and administrative process. Notification is an issue that needs to be focused sensitively on transactions related to taxation process due to the fact that it allows not to use the administrative rights of the accountant in transactions related to the taxation process, but also allows the accountant to use the judicial rights in the tax prosecution process. In this context, the use of administrative rights such as reconciliation and reduction in penalties is only possible after the notification. Besides allowing the interested person to be informed about the legal procedure against him/ her and the issues which are based on these proceedings, notification also allows its addressee to make it possible for the judicial authorities to seek judicial rights against such proceedings and to present their claims to these authorities. In this respect, notification is closely related to right to a fair trial in Article 6 of the European Convention on Human Rights and other rights and principles based on this right.
Keywords: Adil Yargılanma Hakkı Notification; Law and legislation; Notice (Law); Right to a Fair Trial; Taxation; Tebligat; Tebligat hukuku; Turkey; Turkish Tax Law; Türk Vergi Hukuku; Türkiye; Vergilendirme; Yasa ve yasama